What matters most in online learning environments;A New Zealand case study - Siragusa, Lou; Dixon, Robert; Dixon, Kathryn (AARE Inc, 2007)
Universities are under increasing pressure to compete in an environment where globalisation of learning has produced increased numbers of student admissions into courses. Programs can potentially be delivered to offshore partner institutions with little consideration for the contextual or cultural differences between the organisation delivering the program and those grappling with the program content and technology at a distance. The focus of this paper is to describe a small case of students studying within an online adult education program throughout 2005. The case represents a small group of adult learners who embarked upon a Graduate Certificate delivered by an Australian university in New Zealand. Rich qualitative data were collected through a focus group approach facilitated onsite in New Zealand. The results revealed a certain level of discomfort for students when learning through technology, a sense of apprehension when communicating online and varying levels of communication competence which impacted upon the success of the learning experience. The results also indicated that while the sample was determined to succeed in navigating the online environment they considered it to be problematic in terms of the competing demands of family, work and their specific learning styles.